Portrait of a Teach for All (TFA) teacher: Media narratives of the universal TFA teacher in 12 countries - Michelle Gautreaux; Sandra Delgado (Arizona State University, 2016)
This article employs narrative analysis to examine how the media in 12 different countries characterize the Teach for All (TFA) teacher.  Examining mass media narratives in these 12 countries illustrates that there are some remarkable commonalities in the narratives and character portraits co-constructed and propagated by the media. At the core of these narratives is the notion of a problem in education. This problem justifies the creation and emergence of a character, commonly constructed in opposition to traditionally certified teachers, who embodies the characteristics and attributes of the contemporary neoliberal subject. This article discusses the implications of this character's widespread representation; namely, how does the character construction influence the broader public perception about education and how is it contributing to the (re)imagination of the role of the teacher?